Prevalence of Anxiety and Depression Symptoms among Post Bariatric Surgery Patients in Baghdad-Iraq - Mohammed, Abdulnaser M.; Hussien, Amer A.; Mohammed, Abdulrahman M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Obesity is a major public health concern and is on the rise worldwide. Numerous studies revealed that the best method for treating morbid obesity is bariatric surgery, which has indicated its effectiveness in controlling weight. Published studies reported that patients who had undergone bariatric surgery may have psychiatric illnesses when compared to other obese individuals with similar preoperative characteristics.Objectives: Estimate the rates of anxiety and depression among post-operative bariatric surgery patients.Methods: A cross-sectional study on 61 patients was conducted at the bariatric clinic in the Gastroenterology and Hepatology Baghdad Teaching Hospital and the Private Nursing Home Hospital in Medical City, Baghdad, Iraq, from the 1st of April to the 30th of December 2021. Generalised Anxiety Assessment–7 (GAD-7) Scale and Patient Health Questionnaire–9 (PHQ-9) scale were applied to assess these conditions.Results: The prevalence of depression among the studied patients was 32.8%, while the prevalence of anxiety was 44.3%. Marital status, diabetes mellitus, post-operative BMI, and past psychiatric history were significantly associated with depression. Chronic diseases (diabetes mellitus and hypertension), post-operative BMI, and psychiatric history were significantly associated with anxiety.Conclusions: Anxiety was found to be more common than depression among patients who underwent bariatric surgery. Variables predicting both depression and anxiety were diabetes mellitus, post-operative severe obesity, and a history of psychiatric disorders before surgery.